واقع سوء السلوك التنظيمي داخل في المؤسسات العمومية الجزائرية بعض الإدارات العمومية (المدريات) بولاية الوادي نموذجا - منصور, د / بوبكر (Sciences humaines; Vol. 42 (2015): SCIENCES HUMAINES (Novembre ), 2016)
يعد سلوك الفرد داخل التنظيم بمثابة المحرك الأساسي لنشاط هذا التنظيم، ومصدر الحركة فيه،كما يمثل سلوك الفرد الوحدة الأولية التي يقوم عليها سلوك المنظمة، وأن أي محاولة لفهم سلوك الأفراد داخل التنظيم يعتمد بالضرورة على فهم شامل، ودقيق لعلاقات التأثير المتبادل بين خصائص الفرد الذاتية من جهة، وخصائص المنظمة الوظيفية، والتنظيمية، والثقافية من جهة أخرى. ذلك أن الهدف الأساسيَّ من دراسة السلوك الإنساني هو اكتشاف القوى المحركة التي توجه السلوك الإنساني، وتدفعه في مسارات معينة، سواء كانت هذه القوى مرتبطة بالنواحي الشخصية للفرد، أم مرتبطة بالظروف البيئية المحيطة به، وضمن هذا الإطار نحاول في هذا المقال تقديم ملخص بحث حول أشكال سوء السلوك التنظيمي السائدة في الإدارات العمومية الجزائرية ودراسة مختلف المعطيات التي تم رصدها ميدانيا من بعض الإدارات العمومية بولاية الوادي وتفسيرها وفق رؤية تحليلية ونفس- ثقافية. The behaviour of individual in the organization is considered as the principal motor to its activity, and the source of the movement in it. The behaviour of the individual represents the primary unit which the behaviour of the organization is based on. Each attempt to understand the behaviour of individuals into the organization relies necessarily on a comprehensive and accurate understanding of the mutual impact’ s relations between the characteristics of the individual himself on one side, and the functional, organizational and cultural characteristics of the organization on the other side. That’s because the principal aim of studying the human behaviour is to discover the leading forces that guide it and drive it to special tracks , either it was attached to the personal aspects of the individual or to the surrounding environmental conditions. Within this framework , we try in this paper to present a summary of a research about the forms of the organizational misbehaviour prevailing in the Algerian public administration and to study the different field monitored data from some public administrations in the state of El-Oued and to explain it according to an analytical and psycho-cul